An evaluation of the growth and yield of perennial cereals in two contrasting environments - Innes, P. J.; Newell, M. T.; Pembleton, K. G.; Hayes, R. C.; Radanielson, A. M. (Elsevier, 2025)
Perennial cereals have been proposed as an alternative to annual crops in Australian mixed grazing and cropping enterprises. However, there is a lack of data defining suitable regions, and which species may be successfully grown as dual-,purpose grain and fodder crops. This research compared the growth of three candidate perennial cereals, intermediate wheatgrass, mountain rye, and hybrid perennial wheat, to a forage species (tall wheatgrass) and an annual winter wheat. The crops were grown in two contrasting Australian cropping and livestock regions, Cowra in NSW (temperate) and Pittsworth, Queensland (sub-tropical). In year 1 treatments included early, late, and early plus late defoliation, to simulate grazing before reproductive development. Phenology was recorded monthly and the crops harvested each year as the plants reached grain maturity. At Pittsworth defoliation treatments produced no significant effect on yields in year 1. At Cowra, the undefoliated treatments produced the highest biomass and grain yields. Intermediate wheatgrass yield was very low in year 2 at Pittsworth with temperatures > 35°C occurring during early reproductive development. Mountain Rye had slightly higher grain yields, but had longer maturity compared to the annual and hybrid perennial wheat. It was concluded that the longer maturity times of mountain rye and intermediate wheatgrass made them vulnerable to reproductive stage heat and moisture stress, especially at Pittsworth.